Numerical Simulation and Optimization of Sleipner Carbon Sequestration Project - Zhang, Zheming; Agarwal, Ramesh K. (International Journal of Engineering and Technology, 2013)
The capability of accurate numerical simulation and optimization is greatly desired as the technology of geological carbon sequestration (GCS) advances. It can provide quick information for preliminary design of a GCS project. The simulation and optimization results can provide better understanding of the nature of GCS and the uncertainties associated with it and therefore can provide guidelines and the development of best practices for its deployment. In this paper, first the satisfactory history-matching of the Sleipner GCS project is achieved by using the TOUGH2 simulation package. Next, the reservoir engineering technique known as water-alternating-gas (WAG) is applied to the model of the Utsira formation and optimization studies are conducted to determine the optimal WAG operation using the recently developed simulation/optimization code GA-TOUGH2. Results of WAG optimization suggest that in situ CO2 footprint reduction and dissolution acceleration can be achieved while minimizing the water usage.